Association of Physical Activity and Coffee Consumption with Hypertension Incidence Among Productive-Age Adults in Godong I Community Health Center, Grobogan Regency - Lufianti, Anita; Wahyuningsih, Nita; Fitriani, Fitriani; Rahmawati, Rahmawati (LPPM STIKes Muhammadiyah Ciamis, 2025)
Hypertension is a major non-communicable disease that increasingly affects individuals of productive age and contributes to cardiovascular complications such as stroke and heart failure. This study aimed to examine the association between physical activity, coffee consumption, and hypertension incidence among productive-age adults at the Godong I Community Health Center, Grobogan Regency. Objective is to find the relationship between physical activity and coffee consumption with the incidence of hypertension. A quantitative cross-sectional study was conducted among 99 respondents. Data were collected through questionnaires and blood pressure measurements. Statistical analysis was performed using Spearman’s rank correlation test with a significance level of p<0.05. Physical activity (p=0.001) and coffee consumption (p=0.008) showed significant associations with hypertension incidence. Both physical activity and coffee consumption are significantly associated with hypertension among the productive-age population.